A History of Mitchell Park in Three Eras: 1890-2021 - (:unkn) unknown (My University, 2021)
This thesis examines the history of Mitchell Park—and the various iterations of the conservatory it now hosts—across three distinct periods of urban development. Located in Milwaukee, WI, the County-operated institution consists of three conoidal-domes, measuring 140 feet across by 85 feet high (7 stories), each structure protects an acre of soil within; one dome hosting desert flora, a second filled with tropical vegetation, and a third mixed-use ‘show-dome’ able to host rotating exhibitions. The massive civic structures were constructed over nine years, from 1958-1967, as a testament to the industrial might of the growing harbor city. Through a blend of primary and secondary sources, this thesis seeks to provide a more complex and detailed history of Mitchell Park than currently exists. The few historical writings that do exist, do not focus on Mitchell Park exclusively and tend to condense its long history into a one-to-two-page summary. By excavating the past, this thesis identifies and analyzes the social and cultural forces informing park design and development in Milwaukee. More broadly, a close examination of the history of Mitchell Park shows how place can be used as a lens to understand urban change through three distinct eras: Golden Age Milwaukee (1880-1930), Postwar Milwaukee (1945-1972), and Neoliberal Milwaukee (1972-ongoing), and in turn, how each era influenced park design and development. Acting as a symbolic representation of Milwaukee's history and a manifestation of its identity, the story of Mitchell Park is also broadly reflective of the wider urbanization process in the United States. In attempting to trace the mechanisms that shape the city, this thesis explores the history of urban development, and the complex nature of power within the city, through the collection, and juxtaposition, of both primary and secondary sources.